Optimization of β-glucosidase activy in recombinant Saccharomyces cerevisiae strains - Ranwedzi, Ntanganedzeni (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2007.